1999
DOI: 10.1016/s0014-5793(99)01300-9
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies of Escherichia coli biotin synthase: evidence for reversible interconversion between [2Fe‐2S]2+ and [4Fe‐4S]2+ clusters

Abstract: The nature and properties of the iron-sulphur (Fe-S) cluster in as-prepared and reduced biotin synthase of Escherichia coli have been investigated by Mo «ssbauer spectroscopy. Our data clearly demonstrate that in the as-prepared sample, the cluster is present as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 27 publications
9
53
0
Order By: Relevance
“…We confirmed this (2Fe-2S) 2+ to (4Fe-4S) 2+ transformation by addition of dithionite (2 equiv) in a glycerol-containing medium using Mössbauer spectroscopy (38). We could observe the liberation of Fe 2+ (≈ 25%) which was not reincorporated into clusters (note that this experiment was done in a glovebox but without oxygen control).…”
Section: Discussionsupporting
confidence: 65%
“…We confirmed this (2Fe-2S) 2+ to (4Fe-4S) 2+ transformation by addition of dithionite (2 equiv) in a glycerol-containing medium using Mössbauer spectroscopy (38). We could observe the liberation of Fe 2+ (≈ 25%) which was not reincorporated into clusters (note that this experiment was done in a glovebox but without oxygen control).…”
Section: Discussionsupporting
confidence: 65%
“…This conclusion is supported by biochemical experiments, electron paramagnetic resonance, resonance Raman and Mössbauer spectroscopies, and the recently solved 3D structure [20]. The (4Fe-4S) centre is highly oxygen sensitive [21,22], and the as-isolated protein contains uniquely the (2Fe-2S) 2+ cluster. We have also found, studying whole cells overexpressing biotin synthase by Mössbauer spectroscopy, that the two clusters were present, although in different proportions [23].…”
Section: The Nature Of the (Fe-s) Clusters In The Active Form Of Biotmentioning
confidence: 70%
“…A first proposal, based on spectroscopic studies (2), envisioned a (2Fe-2S) center which could, under reducing conditions, convert into one (4Fe-4S) center bridging the two subunits of the dimer (4). This proposal was then challenged when we (7) and others (9) demonstrated that anaerobic preparations of BioB could bind as many as four Fe and four S atoms per monomer in the form of (4Fe-4S) 2+/1+ clusters which undergo degradation into (2Fe-2S) clusters upon exposure to air (7)(8)(9)36). Finally, a recent report from Ugulava et al suggested the presence of two different clusters in biotin synthase, a (4Fe-4S) cluster involved in the conversion of dethiobiotin into a radical and a (2Fe-2S) one proposed to be the source of sulfur atoms for incorporation into this radical (10,11).…”
Section: Discussionmentioning
confidence: 99%